2017
DOI: 10.1093/aob/mcw256
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and histological responses of African rice (Oryza glaberrima) to Meloidogyne graminicola provide new insights into root-knot nematode resistance in monocots

Abstract: Background and Aims The root-knot nematode Meloidogyne graminicola is responsible for production losses in rice (Oryza sativa) in Asia and Latin America. The accession TOG5681 of African rice, O. glaberrima, presents improved resistance to several biotic and abiotic factors, including nematodes. The aim of this study was to assess the cytological and molecular mechanisms underlying nematode resistance in this accession.Methods Penetration and development in M. graminicola in TOG5681 and the susceptible O. sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 57 publications
7
35
1
Order By: Relevance
“…Although RKN infection has been associated with suppression of ET responses (Barcala et al, 2010;Nahar et al, 2011;Kyndt et al, 2012b), patterns of repression or activation have also been observed in both incompatible and compatible interactions between rice and M. graminicola (Petitot et al, 2017). Our data revealed similar patterns, with numerous ET signalling-related proteins and ERF activators up-or downregulated amongst the DEGs.…”
Section: Phytohormone-related Genessupporting
confidence: 74%
“…Although RKN infection has been associated with suppression of ET responses (Barcala et al, 2010;Nahar et al, 2011;Kyndt et al, 2012b), patterns of repression or activation have also been observed in both incompatible and compatible interactions between rice and M. graminicola (Petitot et al, 2017). Our data revealed similar patterns, with numerous ET signalling-related proteins and ERF activators up-or downregulated amongst the DEGs.…”
Section: Phytohormone-related Genessupporting
confidence: 74%
“…Six defense genes were induced in the resistant wheat, but only three were induced in the susceptible cultivar, suggesting that the latter had an attenuated jasmonate signal pathway. A number of studies have linked changes in lignin to both the nematode infection process and to host-nematode interactions [4,6,13,58,76]. Thompson et al [25] found that the resistant landrace IWA8608077 had higher lignin content than the susceptible Louise [77].…”
Section: Genes Associated With Disease Resistance Against Soilborne Pmentioning
confidence: 99%
“…Of the 16 target genes, 12 resulted in reduction in nematode egg masses and/or gall counts in root infection assays when gene function was disrupted. This approach identified novel pathogenicity proteins and narrowed the candidate gene pool to a feasible number for further testing A transcriptome study of root responses to M. graminicola infection was carried out using the resistant African rice, Oryza glaberrima, and a susceptible japonica cultivar of O. sativa [6]. In the resistant rice, nematode penetration was reduced, and females were smaller and laid fewer eggs compared to the susceptible rice.…”
Section: Mining 'Omics Data For Leads To Novel Defense Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of the transcriptome of NPB giant cells at 7 and 14 dpi by using both laser-capture microdissection and RNA-seq indicated that the expression of genes associated with chloroplast biogenesis and tetrapyrrole synthesis was notably changed, while the majority of defense-related genes were extremely suppressed by infection of M. graminicola [11]. Through comparison of the transcriptomes of rice accessions compatibly and incompatibly interacting with M. graminicola at 2, 4 and 8 dpi, 32 potential M. graminicola-resistance-associated genes such as phenylalanine ammonia lyase, thionin and chalcone synthase genes were identified [12]. However, the rice genes underlying resistance to M. graminicola are not yet clear.…”
Section: Introductionmentioning
confidence: 99%